The Effect of the Sustainability of Seribu Galon Program on Household Food Security of Women Farmers in Condongcatur, Sleman Regency - Haunan, Rufaidah; Wati, Ratih Ineke; Untari, Dyah Woro (Agro Ekonomi, 2025)
The increasing scarcity of agricultural land in Condongcatur Village necessitates the sustained fulfillment of food demands. In this context, Seribu Galon program was initiated for Women Farmers Group (WFG) to realize household food security. Sustainability is crucial for guaranteeing the effectiveness of the program and the positive contribution to food security. Therefore, this research aims to assess the sustainability of Seribu Galon program, identify the influencing factors, and the impact on household food security among WFG. Data collection was carried out by interview and observation on 60 members with 12 people drawn from each WFG Teratai Mekar, Lestari, Arum Melati, Dewi Sri and Ijoro by simple random sampling. The data analysis uses the proportion test, multiple linear regression test, and Simple linear regression test. The results showed that most of the sustainability level of the members was high. The average level of sustainability of Seribu Galon Program is 78,72%. Moreover, Seribu Galon program was influenced by age, motivation, as well as role of group and extension workers. And the sustainability of Seribu Galon Program has significant impact on the household food security of women farmers in Condongcatur Village. The research recommends that production and marketing strengthening should be more prioritized to enhance sustainability program, supported by the role of extension workers in monitoring and providing training support.